Application of artificial intelligence in pediatric ophthalmic practice - Grałek, Mirosława; Niwald, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Artificial intelligence (AI) has been developing rapidly in recent years, and finding its way into a number of areas of activity. In ophthalmology, AI has been used since digital information supplied by color fundus photography, optical coherence tomography, computerized visual field testing, and other techniques became available also in this field of medicine. Such information is based on an enormous pool of data forming a basis for machine learning and deep learning. Pediatric ophthalmology is a branch of ophthalmology which has also been increasingly benefiting from the possibilities created by artificial intelligence. The goal of AI in ophthalmology is the early detection of diseases in which prompt treatment can prevent a permanent decrease in visual acuity. AI-based screening in children carries a particular value in preventing and monitoring retinopathy of prematurity, cataract, and myopia. In addition, artificial intelligence is useful in post-operative patient management.